Diversity in decision making for competitive advantage : conceptualising the impact diversity of ideas has on decision making efficiency - Grobler, Jan Dirk (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.